Infliximab Therapeutic Drug Monitoring Changes Clinical Decisions in a Virtual Biologics Clinic for Inflammatory Bowel Disease. Issue 12 (December 2017) - Selinger, Christian P.; Lenti, Marco V.; Clark, Tanya; Rafferty, Helen; Gracie, David; Ford, Alexander C.; O'Connor, Anthony; Ahmad, Tariq; Hamlin, P. John
Abstract : Background: Virtual biologics clinics are often used to review patients with inflammatory bowel disease receiving biological therapy, with decisions whether to continue, switch, or stop therapy made based on review of symptoms, disease history, and investigations. We aimed to investigate whether therapeutic drug monitoring of infliximab (IFX) trough levels and anti-drug antibodies influences decision making within a virtual biologics clinic. Methods: For all patients with inflammatory bowel disease receiving IFX maintenance therapy, 2 decisions were recorded in a preset format. The first decision was based on assessment of clinical details, with clinicians blinded to IFX trough levels and anti-drug antibodies. The second decision was made after unblinding of these data. Results: Among 191 patients (mean age 40 years; 106 (55.5%) male), IFX trough levels were sub-therapeutic in 53 (27.7%) (<2 mg/L), therapeutic in 100 (52.4%), and supra-therapeutic in 38 (19.9%) (>6 mg/L). Anti-drug antibodies were detected in 58 (30.4%), and were >50 AU/mL in 26 (13.6%). Blinded treatment decisions were changed on unblinding these data in 56 cases (29.3%; P < 0.0001). Knowledge of these data led to 7 (3.7%) patients receiving intensified IFX, whereas 33 (17.3%) patients were able to either dose de-escalate or stop IFX. Conclusions: Basing decisions on therapeutic drug monitoring, rather than clinical acumen alone, led to a change in almost one-third of decisions made, offering considerable cost savings and reducing exposure to potentially toxic therapies. Routine therapeutic drug monitoring should be considered an integral part of annual biologics assessment (see Video Abstract, Supplemental Digital Content 1, http://links.lww.com/IBD/B629 ). Abstract : Article first published online 29 September 2017.Supplemental Digital Content is Available in the Text